Satisfaction factors among immobilized orthopedic patients towards care given by nurses - Nik Mohd Hatta, Nik Noor Kaussar; Raja Gopal, Raja Lexshimi (IIUM Press, International Islamic University Malaysia, 2017)
Over the past decade there has been increasing interest in patient satisfaction with nursing care. Quality of care has become one the major aspect that can influence patient satisfaction. The purpose of this study is to evaluate the level of satisfaction among immobilized orthopedics patient towards care given by nurses. These studies also identify the predictor factor that influences level of satisfaction. This cross - sectional study with convenience sampling method was done in two different hospitals in Malaysia which is UKMMC and HKL. The questionnaires distributed to the total 210 respondents (n=80) UKMMC and (n=130) in HKL. The findings show there is high level of satisfaction among immobilizedrthopedic patients towards nursing care in both hospitals 62.5% (n=75) UKMMC and 65.4% (n=). Component of nurse patient relationship also shows the positive relationship between nurse and patient. There are 56.7% (n=119) and 43.3% (n=91) having negative relationship with nurses. The chi square test shows the significant relationship between patients education level and nurse - patient relationship p<0.005 (x2=0.001) and p<0.005 (x2=0.028) towards level of satisfaction. Nurse patient relationship is predictor factor in this study which is 5.7(1/0.175) times more associated with satisfaction of nursing care [OR= 0.175;, 95% CI = 1.799]. Positive relationship between nurse and patient will contributes to the high level of satisfaction towards care given by nurses. Analyzing and understanding the factors that has the greatest impact on overall patient satisfaction will enhance nurses to make some improvements in their care towards